2014
DOI: 10.2152/jmi.61.59
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine protects the small intestinal mucosa in anticancer drug-induced rat enteritis model

Abstract: Supportive therapy during chemotherapy has become essential, but effective preventive therapies to gastrointestinal mucosal injury are few. We investigated the efficacy of glutamine in rat anticancer drug-induced enteritis model. In this study, we used twenty male SD rats. They were divided into control, 5-fluorouracil (5-FU) (orally administered at 20 mg/kg day), 5-FU+glutamine (1000 mg/kg/day) and 5-FU+glutamine+fiber and oligosaccharide (GFO(®)) (1000 mg/kg/day) groups. All groups were sacrificed on day 6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Moreover, in newly weaned piglets, dietary glutamine decreased the proportion of antigen-naïve T cells in the mesenteric lymph nodes (153), which are reported to be elevated in allergic patients and are proposed as an early life marker for future development of allergies (154,155). Finally, dietary glutamine increased the number of IgA-secreting B cells in the small intestine of young mice (156) and enhanced intestinal levels of IgA in various weaning animals (157)(158)(159)(160)(161). Together, these results indicate that glutamine availability influences immune cell populations in developing intestinal tissues, which in turn may influence antimicrobial and anti-allergic immune processes.…”
Section: Impact Of Glutamine On Immune Cell Functionsmentioning
confidence: 74%
“…Moreover, in newly weaned piglets, dietary glutamine decreased the proportion of antigen-naïve T cells in the mesenteric lymph nodes (153), which are reported to be elevated in allergic patients and are proposed as an early life marker for future development of allergies (154,155). Finally, dietary glutamine increased the number of IgA-secreting B cells in the small intestine of young mice (156) and enhanced intestinal levels of IgA in various weaning animals (157)(158)(159)(160)(161). Together, these results indicate that glutamine availability influences immune cell populations in developing intestinal tissues, which in turn may influence antimicrobial and anti-allergic immune processes.…”
Section: Impact Of Glutamine On Immune Cell Functionsmentioning
confidence: 74%
“…Targets to increase secretion of intestinal SIgA are promising and directed at mitigating pathogenesis of diseases. Compelling evidence from well-designed investigations have shown that glutamine supplementation increases the abundance of SIgA in the intestine in various hosts, including rats (4, 5), mice (6, 7), Chinese Holstein calves (8), pigs (9), humans (10), and even broiler chickens (11). Similarly, we found that glutamine supplementation increases SIgA in the luminal contents of the jejunum and ileum, and the number of IgA + plasma cells in the ileum in mice (12).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, secretory IgA concentrations were lower in the 5-FU treated groups, and the EPA/DHA-rich diet resulted in higher IgA concentrations than the other diets, suggesting a protective and preserved effect on intestinal immunity. In this study, we measured IgA in intestinal washing according to our previous work [23] but could not provide the variability of the assay in this matrix.…”
Section: Discussionmentioning
confidence: 99%